Mainshock‐aftershock state‐dependent fragility curves: A case of wood‐frame houses in British Columbia, Canada. (4th March 2020) - Zhang, Lizhong; Goda, Katsuichiro; De Luca, Flavia; De Risi, Raffaele
Summary: During a mainshock‐aftershock (MSAS) sequence, there is no time to retrofit structures that are damaged by a mainshock; therefore, aftershocks could cause additional damage. This study proposes a new approach to develop state‐dependent fragility curves using real MSAS records. Specifically, structural responses before and after each event of MSAS sequences are used to obtain statistical relationships among the engineering demand parameter prior to the seismic event ( pre‐EDP ), the intensity measure of the seismic event ( IM ), and the engineering demand parameter after the seismic event ( post‐EDP ). The developed fragility curves account for damage accumulation, providing the exceeding probability of damage state (DS) given the IM of the event and the DS of the structure prior to the seismic excitation. The UBC‐SAWS model, which was developed for wood‐frame houses in British Columbia, Canada, is considered as a case study application. Results indicate that for the examined structural typology, state‐dependent fragility curves based on residual interstorey drift ratio ( pre‐EDP ), peak ground velocity ( IM ), and maximum inter‐storey drift ratio ( post‐EDP ) are the best choice to characterise the cumulative damage effect. An illustration of the developed fragility curves is provided by considering a hypothetical MSAS scenario of a M w 9.0 Cascadia mainshock triggering a M w 6.0 crustal event in the Leech River fault, affecting wooden houses in Victoria, Canada. The MSAS scenario increases Yellow tags (restricted access) by 12.3% and Red tags (no access) by 4.8%.